Fulminant hepatitis: a clinical review of 11 years - Anna Sara Shafferman Levin; Antonio Alci Barone; Mario Shiroma (Revista do Instituto de Medicina Tropical de São Paulo, 1989)
24 cases of fulminant hepatitis (FH) hospitalized in the Clínica de Doenças Infecciosas e Parasitárias do Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo during the period from January 1976 to December 1986 were reviewed from their clinical, epidemiological and laboratorial aspects. 88% of the patients died; 20 patients (83%) presented hemorrhages and, of these, 19 died. Bacterial infections occurred in 14 patients (58%) all of whom died. Ascitis was noted in 3 cases; cerebral edema was present in 16 cases. Maximal ALT levels for each patient during hospitalization ranged widely from 81 to 4,460 UI/l. Thirteen patients presented high creatinine levels (54%). Prothrombin time activity ranged from 2.1% to 67%. Fever was present in 20 cases (83%). Encephalopathy occurred within the first 2 weeks of illness in 72% of the cases. In 7 cases other illnesses were present. The etiology could not be determined in 13 cases. In 3 cases it was due to yellow fever and 6 cases were caused by viruses other than yellow fever. In one case the cause was drug usage and in another case, possibly alcohol. The authors believe that the clinical definition of FH requires further discussion before it is established. In this study FH is a young person's disease. The mortality found was similar to that by other authors. Factors that contributed to death were: hemorrhages and bacterial infection. Factors that worsened the prognosis of hepatitis were: associated illnesses and surgical procedure. The levels of ALT during hospitalization did not correlate well with the severity of the hepatitis. The authors believe that yellow fever should be considered a cause of FH where the clinical picture meets the criteria for such, although its mechanisms of encephalopathy remain obscure. The clinical details of the 3 cases of yellow fever are presented.